Enhanced development of functional human NK cells in NOD‐scid‐IL2rgnull mice expressing human IL15. Issue 9 (12th August 2022) - Aryee, Ken‐Edwin; Burzenski, Lisa M.; Yao, Li‐Chin; Keck, James G.; Greiner, Dale L.; Shultz, Leonard D.; Brehm, Michael A.
Abstract: Human innate immunity plays a critical role in tumor surveillance and in immunoregulation within the tumor microenvironment. Natural killer (NK) cells are innate lymphoid cells that have opposing roles in the tumor microenvironment, including NK cell subsets that mediate tumor cell cytotoxicity and subsets with regulatory function that contribute to the tumor immune suppressive environment. The balance between effector and regulatory NK cell subsets has been studied extensively in murine models of cancer, but there is a paucity of models to study human NK cell function in tumorigenesis. Humanized mice are a powerful alternative to syngeneic mouse tumor models for the study of human immuno‐oncology and have proven effective tools to test immunotherapies targeting T cells. However, human NK cell development and survival in humanized NOD‐ scid‐IL2rg null (NSG) mice are severely limited. To enhance NK cell development, we have developed NSG mice that constitutively expresses human Interleukin 15 (IL15), NSG‐Tg(Hu‐IL15). Following hematopoietic stem cell engraftment of NSG‐Tg(Hu‐IL15) mice, significantly higher levels of functional human CD56+ NK cells are detectable in blood and spleen, as compared to NSG mice. Hematopoietic stem cell (HSC)‐engrafted NSG‐Tg(Hu‐IL15) mice also supported the development of human CD3+ T cells, CD20+ B cells, and CD33+ myeloid cells. Moreover, the growth kinetics of a patient‐derived xenograft (PDX) melanoma were significantly delayed in HSC‐engrafted NSG‐Tg(Hu‐IL15) mice as compared to HSC‐engrafted NSG mice demonstrating that human NK cells have a key role in limiting the tumor growth. Together, these data demonstrate that HSC‐engrafted NSG‐Tg(Hu‐IL15) mice support enhanced development of functional human NK cells, which limit the growth of PDX tumors.